2017
DOI: 10.1161/hypertensionaha.116.08560
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction of Hypertension and Diabetes in Promoting Kidney Injury and the Role of Endoplasmic Reticulum Stress

Abstract: Diabetes mellitus and hypertension are major risk factors for chronic kidney injury, together accounting for >70% of end-stage renal disease. In this study, we assessed interactions of hypertension and diabetes in causing kidney dysfunction and injury and the role of endoplasmic reticulum (ER) stress. Hypertension was induced by aorta constriction (AC) between the renal arteries in 6-month old male Goto-Kakizaki (GK) type 2 diabetic and control Wistar rats. Fasting plasma glucose averaged 162±11 and 87±2 mg/dL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 51 publications
5
55
0
Order By: Relevance
“…Schematic of the developed approach and proposed synergistic effects of diabetes and hypertension on the kidney (adopted from 3 ). As shown in this figure, increased blood pressure (BP) followed aorta constriction (AC) in non-diabetic kidney and normal BP in diabetic kidneys conditions result in mild kidney injury.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Schematic of the developed approach and proposed synergistic effects of diabetes and hypertension on the kidney (adopted from 3 ). As shown in this figure, increased blood pressure (BP) followed aorta constriction (AC) in non-diabetic kidney and normal BP in diabetic kidneys conditions result in mild kidney injury.…”
Section: Figurementioning
confidence: 99%
“…In this issue of the Hypertension , Wang and colleagues explored interactions of hypertension and diabetes, and their contribution to kidney injury 3 . This study is highly significant from both conceptual and technical perspectives.…”
mentioning
confidence: 99%
“…The coexistence of diabetes mellitus and hypertension increases the risk for onset and progression of chronic renal diseases. 12 Wang et al showed that diabetes mellitus and hypertension interact synergistically to promote oxidative stress and ER stress, thereby leading to progressive renal injury in a rat model of mild type 2 diabetes mellitus combined with hypertension. 12 Treatment of hypertensive-diabetic rat with ER stress inhibitor, tauroursodexycholic acid (TUDCA) for 6 weeks decreases blood pressure, proteinuria, glomerular injury, and oxidative stress, while increasing glomerular filtration rate in the kidneys, suggesting that diabetes mellitus and hypertension synergistically cause renal dysfunction and injury via induction of ER stress.…”
Section: -8mentioning
confidence: 99%
“…12 Wang et al showed that diabetes mellitus and hypertension interact synergistically to promote oxidative stress and ER stress, thereby leading to progressive renal injury in a rat model of mild type 2 diabetes mellitus combined with hypertension. 12 Treatment of hypertensive-diabetic rat with ER stress inhibitor, tauroursodexycholic acid (TUDCA) for 6 weeks decreases blood pressure, proteinuria, glomerular injury, and oxidative stress, while increasing glomerular filtration rate in the kidneys, suggesting that diabetes mellitus and hypertension synergistically cause renal dysfunction and injury via induction of ER stress. 12 Autophagy functions as a pivotal protein degradation machinery that degrades and removes misfolded and aggregated proteins and damaged organelles under both physiological and pathological conditions.…”
Section: -8mentioning
confidence: 99%
See 1 more Smart Citation